Oxytocin affects spontaneous neural oscillations in trauma-exposed war veterans - Eidelman-Rothman, Moranne; Goldstein, Abraham; Levy, Jonathan; Weisman, Omri; Schneiderman, Inna; Mankuta, David; Zagoory-Sharon, Orna; Feldman, Ruth (Frontiers in Behavioral Neuroscience, 2015)
Exposure to combat-related trauma often leads to lifetime functional impairments. Previous research demonstrated the effects of oxytocin (OT) administration on brain regions implicated in post-traumatic stress disorder (PTSD); yet OT’s effects on brain patterns in trauma-exposed veterans have not been studied. In the current study the effects of oxytocin on spontaneous brain oscillatory activity were measured in 43 veterans using magnetoencephalography (MEG): twenty-eight veterans who were exposed to a combat-related trauma and 15 trauma-unexposed controls. Participants participated in two experimental sessions and were administered OT or placebo in a double-blind, placebo-control, within-subject design. Following OT/placebo administration, participants underwent a whole-head MEG scan. Plasma and salivary OT levels were assessed each session. Spontaneous brain activity measured during a two-minute resting period was subjected to source-localization analysis. Trauma-exposed veterans showed higher resting-state alpha (8-13 Hz) activity compared to controls in the left dorsolateral prefrontal cortex, specifically in the superior frontal gyrus and the middle frontal gyrus, indicating decreased neural activity in these regions. The higher alpha activity was ‘normalized’ following OT administration and under OT, group differences were no longer found. Increased resting-state alpha was associated with lower baseline plasma OT, reduced salivary OT reactivity, and more re-experiencing symptoms. These findings demonstrate effects of OT on resting-state brain functioning in prefrontal regions subserving working memory and cognitive control, which are disrupted in PTSD. Results raise the possibility that OT, traditionally studied in the social context, may also enhance performance in cognitive tasks associated with working memory and cognitive control following trauma exposure.